2013
DOI: 10.1159/000354433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DHA and CoenzymeQ10 Against A�- and Zinc-Induced Mitochondrial Dysfunction in Human Neuronal Cells

Abstract: Background: Beta-amyloid (Aβ) protein is a key factor in the pathogenesis of Alzheimer's disease (AD) and it has been reported that mitochondria is involved in the biochemical pathway by which Aβ can lead to neuronal dysfunction. Coenzyme Q10 (CoQ10) is an essential cofactor involved in the mitochondrial electron transport chain and has been suggested as a potential therapeutic agent in AD. Zinc toxicity also affects cellular energy production by decreasing oxygen consumption rate (OCR) and ATP turnover in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Our lysotracker labelling further revealed that pepstatin A partly attenuated diffuse labelling of neurons observed after Ab treatment ( Figure 5I-K). In parallel, we showed that Ab 1-42 toxicity, as reported in earlier studies [76,77], was significantly attenuated following treatment with antioxidant CoQ10. Concurrently the levels of carbonylated proteins and CatD were reduced ( Figure S4).…”
Section: Protective Effects Of Pepstatin a Against Ab 1-42induced Toxsupporting
confidence: 87%
“…Our lysotracker labelling further revealed that pepstatin A partly attenuated diffuse labelling of neurons observed after Ab treatment ( Figure 5I-K). In parallel, we showed that Ab 1-42 toxicity, as reported in earlier studies [76,77], was significantly attenuated following treatment with antioxidant CoQ10. Concurrently the levels of carbonylated proteins and CatD were reduced ( Figure S4).…”
Section: Protective Effects Of Pepstatin a Against Ab 1-42induced Toxsupporting
confidence: 87%
“…These findings indicate that Abeta induced cell death in neuro-2A cells. Recently, unsaturated fatty acids including DHA and EPA have been shown to protect against AD and neuronal cell damage (Sadli et al 2013;Swanson et al 2012). Our results indicate that the cell viability of Abita-treated neuro-2A cells could be improved by treatment with extracts of Nannochloropsis oceanica from Group II (Fig.…”
Section: Crude Fat Dha and Epa Generations In Nannochloropsis Oceanicamentioning
confidence: 58%
“…These omega-3 unsaturated fatty acids have been reported to protect against Alzheimer's disease (AD) (Sadli et al 2013;Sahlin et al 2007), and against oxidative stress in neural cells (Yang et al 2012). Recently, omega-6 unsaturated fatty acids such as arachidonic acid and linoleic acid have been found to play a role in the development of inflammation (Al-Taan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The third interesting finding in the current study is that ZnO NPs-induced dysregulation of iron homeostasis partially due to dissolved Zn 2+ . Although Zn 2+ is an inert cation and does not undergo a redox reaction, Zn 2+ overload is closely related to ROS and subsequently mitochondrial injuries 47,48 . The aberrant homeostasis of transition metal ions, e.g., Fe 2+ /Fe 3+ , Zn 2+ , and Ca 2+ , plays important roles in the pathogenesis of various diseases.…”
Section: Discussionmentioning
confidence: 99%